Combating Cyber Crime From The Perspective Of Islamic Criminal Law - Aicha Azdina Adly Fesya; Rizky Zaidan Ketaren (AT-TAFAHUM: Journal of Islamic Law, 2022)
This article aims to analyze the concept of cybercrime prevention from the perspective of Islamic criminal law and examine its relevance to the development of modern digital crime. The research method used is normative legal research with a conceptual approach and a legislative approach. The data used consists of primary, secondary, and tertiary legal materials analyzed qualitatively. The results of the study indicate that although cybercrime is not explicitly recognized in classical Islamic criminal law literature, the basic principles of jarimah, particularly in the category of ta'zir, can be used to qualify various forms of cybercrime.